Advanced engineering dynamics - Harrison, H. R. (Arnold ; Wiley, 1997)
'Advanced Engineering Dynamics' bridges the gap between elementary dynamics and advanced specialist applications in engineering. It begins with a reappraisal of Newtonian principles before expanding into analytical dynamics typified by the methods of Lagrange and by Hamilton's Principle and rigid body dynamics. Four distinct vehicle types (satellites, rockets, aircraft and cars) are examined highlighting different aspects of dynamics in each case. Emphasis is placed on impact and one dimensional wave propagation before extending the study into three dimensions. Robotics is then looked at in det.
Keywords: Dynamics.; Mechanics, Applied.; elektronické knihy; electronic books